AN OT ACCOUNT OF PHONOTACTIC AND CODA NEUTRALIZATION OF ENGLISH LOANS IN PILIBHIT HINDI-URDU - Hamid Raza, Mohd (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2020)
This paper provided the basic information of the phonological processes as the Coda Neutralization and Phonotactics of English Loans in Pilibhit Hindi-Urdu within the framework of Optimality Theory (OT). The objectives of this paper were to represent the aspects of the coda neutralization in the sense of voiced obstruent segment becomes voiceless obstruent segment in the final syllable structure of the loanwords, and the consonant clusters break within the insertion of an extraneous segment in any location of the English Loans in Pilibhit Hindi-Urdu. In the another framework, this paper revealed the phenomena of devoicing features of coda consonants and the grades of the additional segments in Pilibhit Hindi-Urdu loanwords within the principles of Optimality Theory (Prince & Smolensky, 1993). The central idea of this paper was to explore the process of conflicts between the candidates at the surface level and reflects the properties of the input candidate by the observation of the constraint rankings. In this study, it was propounded the effective formalities of the hierarchy of the constraint rankings and drew one of the best candidates as an optimal candidate out of the output candidates from English loans in Pilibhit Hindi-Urdu. The groundwork of this paper was related to the significant aspects of the English loans that were adapted within the addition, insertion, or deletion of the segments in Pilibhit Hindi-Urdu. In this paper, it was also determined the facts of the coda devoicing of the speech segments in terms of neutralization at the end of the syllable structure of English loans in Pilibhit Hindi-Urdu.